Quality control of hazelnut-based spreads: 1H TD-NMR transverse relaxation - Trapp, Lena; Kafashian, Saghar; Schacht, Hilke; Nirschl, Hermann; Guthausen, Gisela (Frontiers in Food Science and Technology, 2024)
Hazelnut-based spreads are very popular, and they are available in a variety of compositions and prices. They, therefore, require detailed quality control and reliable fraud detection regarding the substitution of high-cost cocoa butter. Transverse relaxation measured via 1H time domain NMR (TD-NMR) is an approach that is compatible with industrial quality control but allows an in-depth insight into the materials. When transverse relaxation is measured as a function of temperature in a moderate range T ϵ [253, 353] K, the melting of cocoa butter and palm oil can be studied. The observations can be taken as a basis for quality control as the prices of these two components are significantly different. Fats introduce different qualities to the spreads in addition. This paper describes the experimental procedure and the findings on a spread sample basis with a considerable span width regarding the ingredients of commercially available hazelnut-based spreads.